Empathy and psychopathology in children and adolescents: the role of parental mental illness and emotion regulation - Luczejko, Arleta A.; Hagelweide, Klara; Stark, Rudolf; Weigelt, Sarah; Christiansen, Hanna; Kieser, Meinhard; Otto, Kathleen; Reck, Corinna; Steinmayr, Ricarda; Wirthwein, Linda; Zietlow, Anna-Lena; Schwenck, Christina; et al. (Frontiers in Psychiatry, 2024)
Objective: Although empathy is known to be a strength, recent studies suggest that empathy can be a risk factor for psychopathology under certain conditions in children. This study examines parental mental illness as such a condition. Further, it aims to investigate whether maladaptive emotion regulation (ER) mediates the relationship between empathy and psychopathological symptoms of children. Methods:Participants were 100 children of parents with a mental illness (55 % female) and 87 children of parents without a mental illness (50 % female) aged 6 -16 years and their parents. Results: Greater cognitive empathy was related to more psychopathological symptoms in COPMI, but not in COPWMI. In addition, in COPMI maladaptive ER mediated this relationship. In contrast, greater affective empathy was associated with more psychopathological symptoms regardless of whether parents had a mental illness.Our findings highlight the importance of implementing preventive programs for COPMI that specifically target the reduction of maladaptive ER.